Applying the Verona coding definitions of emotional sequences (VR-CoDES) to code medical students' written responses to written case scenarios: Some methodological and practical considerations. Issue 2 (February 2017) - Ortwein, Heiderose; Benz, Alexander; Carl, Petra; Huwendiek, Sören; Pander, Tanja; Kiessling, Claudia
Highlights: VR-CoDES-P were applicable to code written responses of medical students. 74.6% of responses included "reducing space" statements. Using VR-CoDES-P is feasible when coding "providing" and "reducing space" responses. Students need precise instructions on how to respond in the given test format. Abstract: Objective: To investigate whether the Verona Coding Definitions of Emotional Sequences to code health providers' responses (VR-CoDES-P) can be used for assessment of medical students' responses to patients' cues and concerns provided in written case vignettes. Methods: Student responses in direct speech to patient cues and concerns were analysed in 21 different case scenarios using VR-CoDES-P. Results: A total of 977 student responses were available for coding, and 857 responses were codable with the VR-CoDES-P. In 74.6% of responses, the students used either a "reducing space" statement only or a "providing space" statement immediately followed by a "reducing space" statement. Overall, the most frequent response was explicit information advice (ERIa) followed by content exploring (EPCEx) and content acknowledgement (EPCAc). Discussion: VR-CoDES-P were applicable to written responses of medical students when they were phrased in direct speech. The application of VR-CoDES-P is reliable and feasible when using the differentiation of "providing" and "reducing space" responses. Communication strategies described by students in non-direct speech were difficult to code and produced many missings. Practice implications: VR-CoDES-P are useful for analysis of medical students' written responses when focusing on emotional issues. Students need precise instructions for their response in the given test format.